خۆگونجاندنی كۆمەڵایەتی بەساڵاچووان لە نێو خێزاندا توێژینەوەیەكی كۆمەڵایەتی مەیدانیە لە شاری سلێمانیدا ئەنجامدراوە - محەمەد, كوردوستان عومەر; حسێن, شۆخان محمود (Sulaimani Journal for Humanities, 2025)
It is obvious that human life goes through many different stages, each stages carries specific characteristics that distinguish it from its peers from the stages. But despite these alterations and differences, there are essential and necessary participants, none of which can condone and impose upon themselves. Life cannot go on without a smooth natural continuation. The most important of these is the phenomenon of human adaptation to the social environment . But this does not mean that people who adapt to the environment, and in all its social, psychological, personality and other forms, are completely protected from most social problems and obstacles, and are not affected by the difficulties of life. But it is better to manage the life with them than others who cannot survive with them and with the social environment. The responding of the socially adaptive person for the problems and changes that occur around him, is a soft health response stemming from his realistic view of life and far from fantasies and perceptions that can only be achieved in dreams. Therefore, in this research, we sought to link this variable, social adjustment, which is one of the most important dimensions of adaptation, to one of the most important stages of human life, which is aging. The person, who comes to this stage, holds usual characteristics, skills and experiences that make him socially capable and at the highest levels able to continue and interact with life, and in its dimensions, in a smooth, calm and healthy manner. This research is divided into two parts. The first Part includes three sections. The first one deals with the basic components of research, the second deals with (changes in aging and their problems, as well as family functions), and the third deals with the relationship between social adjustment for adults Age by a set of variables and theories of its own, ie by social adjustment). The second part consists of two sections, the first one deals with the (methodological framework of the research), and the second deals with (presenting and discussing the results of the research). The most important results of the research, following the statistical analysis of the contents, are: 1. The social adjustment of the elderly has reached the highest levels in the Kurdish family. 2. There are specific cases and conditions in the Kurdistan Region that have negatively affected the social adjustment of older persons. 3. There are specific cases and psychological conditions that positively affected the social adjustment of the elderly in the Kurdistan Region. 4. The variable of age had no effect on respondents' responses to the social adjustment process in the Kurdistan Region. 5. There are significant statistical dissimilarities and differences between the responses of the respondents, according to the variables (gender, marital status and standard of living) towards the social adjustment process in the Kurdistan Region. Finally, the research presented a set of proposals and recommendations related to the subject, the list of sources used by the researchers and the necessary supplements, as well as two summaries of the research in Arabic and English.